Chapter 17: Navigating turbulence for sustainability - Shipton, Leah (Edward Elgar Publishing, 2023)
Although escalating planetary turbulence threatens to destabilize political and economic systems, it also has the potential to inspire new ways to halt destructive practices and more toward more sustainable and just ways of governing world politics. This chapter presents a thematic summary of possible pathways for such a transformation. It begins by briefly exploring barriers to effective governance through turbulence, such as the tendency for path dependency to keep ineffective institutions intact, before turning to consider ways to improve global governance during times of extreme turbulence. Effective governance, the chapter suggests, features decisionmakers who accept uncertainty, think holistically, and facilitate participatory policymaking; it further necessitates justice-oriented and flexible institutions enabling creative experimentation and minimizing unintended consequences. The chapter emphasizes, too, the value of reflexive practice to help reveal failures and uncover alternatives, as well as the importance of transnational civil society mobilization for facilitating a transition to effective governance and a broader systemic transformation of the world order.